2020
DOI: 10.1007/s12209-020-00253-9
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Calculations for the Evaluation of FePS3 as a Promising Anode for Mg Ion Batteries

Abstract: FePS 3 , a classical 2D layered material with transition metal phosphorous trichalcogenides, was investigated as an anode material for Mg ion batteries. We used density functional theory to calculate the Mg storage properties of FePS 3 , such as Mg adsorption energy, theoretical specific capacity, average voltage, diffusion energy barriers, volume change, and electronic conductivity. The theoretical specific capacity of the FePS 3 monolayer is 585.6 mA h/g with a relatively low average voltage of 0.483 V (vs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…In the case of the Si 2 BN-H ribbon, the Mg adsorption shows rather a larger volumetric expansion up to 120% for the full edge coverage case (15 Mg) as shown in Figure k. With an increase in Mg concentration, more valence electrons between Mg atoms and the Si 2 BN-H ribbon induce more stresses, and consequently, to retain the crystallinity, there is breaking of a few bonds to eliminate the stresses, which results in large volume expansion in the Si 2 BN-H framework . In support, we have measured the interatomic distances for Si 2 BN/Si 2 BN-H ribbons for various Mg coverages.…”
Section: Results and Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In the case of the Si 2 BN-H ribbon, the Mg adsorption shows rather a larger volumetric expansion up to 120% for the full edge coverage case (15 Mg) as shown in Figure k. With an increase in Mg concentration, more valence electrons between Mg atoms and the Si 2 BN-H ribbon induce more stresses, and consequently, to retain the crystallinity, there is breaking of a few bonds to eliminate the stresses, which results in large volume expansion in the Si 2 BN-H framework . In support, we have measured the interatomic distances for Si 2 BN/Si 2 BN-H ribbons for various Mg coverages.…”
Section: Results and Discussionmentioning
confidence: 70%
“…With an increase in Mg concentration, more valence electrons between Mg atoms and the Si 2 BN-H ribbon induce more stresses, 59 and consequently, to retain the crystallinity, there is breaking of a few bonds to eliminate the stresses, which results in large volume expansion in the Si 2 BN-H framework. 28 In support, we have measured the interatomic distances for Si 2 BN/Si 2 BN-H ribbons for various Mg coverages. The average neighboring distance between Mg and Si 2 BN ribbons (for 2-Mg) was 2.3323 Å, while at 15 Mg concentrations, it was 3.265 Å.…”
Section: Mg Adsorption On the Hydrogen-passivated Si 2 Bn Ribbon To U...mentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, an emerging multielement 2D layered material is metal phosphorus trichalcogenides (MPTs), which is one of the van der Waals layered materials first discovered in the late 19th century by Friedel and Ferrand. The framework layers of [P 2 S 6 ] 4– or [P 2 Se 6 ] 4– are weakly bonded to metal cations (M II or M I M III ) through van der Waals interactions.…”
Section: Intrinsic Photonic Properties Of 2d Materialsmentioning
confidence: 99%
“…Also, some Mg binary and ternary compounds have been screened with DFT in order to identify potential coating materials for Mg batteries that could separate the distinct chemistries of the metal‐anode and the cathode materials from the electrolyte for the sake of stability. [ 168 ] The properties of some alternative anodes for emerging MIB has been studied with DFT, e.g., FePS 3 , [ 169 ] and Mg 3 Bi 2 , [ 170 ] where has been revealed that relativistic spin‐orbit coupling effects are linked to low Mg migration barriers. Due to the difficulties in finding suitable compatible cathodes with Mg anode, most reports have focused on computing the redox reaction mechanism, electrochemical and thermodynamic properties of potential suitable materials such as MnSiO 4 olivines, [ 171 ] tavorite‐FeSO 4 F, [ 172 ] VPO 4 F [ 173 ] or V 2 O 5 [ 174 ] and on how to fine‐tune the composition (e.g., by hydrogenation) to improve their electrochemical performances.…”
Section: Materials Optimization and Characterizationmentioning
confidence: 99%